2013
DOI: 10.1002/cne.23231
|View full text |Cite
|
Sign up to set email alerts
|

Delayed and asynchronous ganglionic maturation during cephalopod neurogenesis as evidenced by Sof‐elav1 expression in embryos of Sepia officinalis (Mollusca, Cephalopoda)

Abstract: Among the Lophotrochozoa, centralization of the nervous system reaches an exceptional level of complexity in cephalopods, where the typical molluscan ganglia become highly developed and fuse into hierarchized lobes. It is known that ganglionic primordia initially emerge early and simultaneously during cephalopod embryogenesis but no data exist on the process of neuron differentiation in this group. We searched for members of the elav/hu family in the cuttlefish Sepia officinalis, since they are one of the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Sof‐pax3/7 expression provided new insights into the differentiation of the epidermis, and the expression of Sof‐elav1 , a member of the elav/hu family and one of the first genetic markers of postmitotic neural cells in metazoans (Campos et al, ; Sakakibara et al, ; Buresi et al, ), permitted early labelling of developing neurons in S. officinalis . Expression patterns of Sof‐elav1 thus provided a new perspective of the early development of the peripheral nervous system, as they did previously for the developing central nervous system of this organism (Buresi et al, ). Here, Sof‐elav1 expression demonstrates that the two developing olfactory organs were the first ectodermal sensory structures in which differentiating neurons were detected, at about stage 16 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sof‐pax3/7 expression provided new insights into the differentiation of the epidermis, and the expression of Sof‐elav1 , a member of the elav/hu family and one of the first genetic markers of postmitotic neural cells in metazoans (Campos et al, ; Sakakibara et al, ; Buresi et al, ), permitted early labelling of developing neurons in S. officinalis . Expression patterns of Sof‐elav1 thus provided a new perspective of the early development of the peripheral nervous system, as they did previously for the developing central nervous system of this organism (Buresi et al, ). Here, Sof‐elav1 expression demonstrates that the two developing olfactory organs were the first ectodermal sensory structures in which differentiating neurons were detected, at about stage 16 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The 687-bp fragment of Sof-elav1 was found to be orthologous to the neurogenic member of the elav/hu family (accession No. HE956712.1; see Buresi et al, 2013). The 783-bp fragment of Sof-pax3/7 (accession No.…”
Section: Materials and Methods Animal Care And Staging Of Embryosmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, adult neuroanatomy of multiple cephalopod species has been well described (Young, 1962a(Young, ,b, 1971Nixon and Young, 2003;Wild et al, 2015). Despite these elegant studies, gene expression is only now being explored during development, and detailed molecular and genomic analyses of cephalopod organogenesis are in their infancy Hartmann et al, 2003;Lee et al, 2003;Baratte et al, 2007;Farfán et al, 2009;Navet et al, 2009;Buresi et al, 2012Buresi et al, , 2013Buresi et al, , 2016Ogura et al, 2013;Focareta et al, 2014;Peyer et al, 2014;Wollesen et al, 2014;Yoshida et al, 2014;Shigeno et al, 2015;Wollesen et al, 2015). The cephalopod eye is a single-chambered eye generated from an internalization of the optic placode (Gilbert et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…This study focused on three genes associated with early tissue speciation. Previous studies have identified many genes implicated in cephalopod limb morphogenesis; future experimentation would especially benefit from timepoint‐ and treatment‐specific profiles, with particular emphasis on genes associated with nervous precursor distribution and development of complex sensory and neurological structures (Baratte & Bonnaud, ; Bassaglia et al, ; Buresi, Baratte, Da Silva, & Bonnaud, ; Buresi, Canali, Bonnaud, & Baratte, ; Buresi, Croll, Tiozzo, Bonnaud, & Baratte, ; Focareta, Sesso, & Cole, ; Zhang & Tublitz, ), as well as muscle (Bassaglia et al, ; Fossati et al, ; Navet et al, ; Zullo et al, ) and endothelium (Focareta & Cole, ). Additional genes of interest should be garnered from the available studies in models across taxa (Fei et al, ; Godwin et al, ; Kawakami et al, ; Uygur & Lee, ; Wischin et al, ); ideally strategies utilizing transcriptomic or single‐cell RNA sequencing could be compared on both amputated and regenerated limb tips to provide greater clarity on intraindividual variation in expression based on injury‐naïve and regenerating conditions.…”
Section: Resultsmentioning
confidence: 99%